Catch you later, traitor - Avi, 1937- (Chapel Hill, North Carolina : Algonquin Young Readers, 2015)
"It's 1951, and twelve-year-old Pete Collison is a regular kid in Brooklyn, New York, who loves Sam Spade detective books and radio crime dramas. But when an FBI agent shows up at Pete's doorstep, accusing Pete's father of being a Communist, Pete is caught in a real-life mystery. Could there really be Commies in Pete's family?"--
Includes bibliographical references.
Keywords: Communism -- Juvenile fiction; Families -- Fiction; Brooklyn (New York, N.Y.) -- History -- 20th century -- Juvenile fiction; Communism -- Fiction; Families -- Fiction; Brooklyn (New York, N.Y.) -- History -- 20th century -- Fiction